Web development with Microsoft resources (Sams.net, 1996)
Nowhere else can readers find one resource on combined Microsoft Internet products and how to utilize them to build and connect databases to the World Wide Web. Includes coverage of hot new products, such as Internet Studio and Internet Information Server. The author is James J. Townsend, president of Information Strategies, a Microsoft Solution Provider in Washington, D.C.